Intuitive human centric governance of pervasive computing environments - O'Donnell, Anthony (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
Pervasive computing proposes that in the future, human beings will be immersed in a technology rich environment, where computing power will be embedded in devices all around us. This thesis examines how such technology rich environments can be effectively governed so that they meet the demands and expectations of the users that they will support.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin